Impact of the use of selected Youtube videos to enhance the speaking performance on a2 efl learners of an ecuadorian public high school - Galán Cherrez, Nefi Manuel; Maya Montalvan, Jeimi Patricia; Garcia Brito, Oswaldo Edison; Montece Ochoa, Steffany Katherine (RECIMUNDO, 2018)
The present research study aims to evaluate the impact of the use of selected YouTube videos for enhancing learners’ speaking performance in English foreign learners (EFL) of A2 level at an Ecuadorian public high school. Normally, by the time Ecuadorian public high school students end their senior year, they are not yet able to effectively communicate in English. Consequently, the requirements established in the curriculum by the Ecuadorian Ministry of Education regarding English teaching as a foreign language are not being successfully accomplished. It is believed that scaffolding speaking lessons with the aid of audio visual materials may bring about effective results regarding communicative performance. Subsequently, quantitative and qualitative instruments will gather data for its coding and analysis. In addition, results suggest that selected YouTube videos bring positive results if classes are elaborated with before, during and after video communicative tasks. Last but not least, implications indicate that classroom environment may affect students’ performance.